2023
DOI: 10.1007/s10342-023-01578-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil C stock and C to N ratio of soil organic matter under mixed pine-beech forests at different scales

Marina Getino-Álvarez,
Roberto San-Martin,
Hans Pretzsch
et al.

Abstract: Healthy soils are the second C sink on Earth, and this sink could last for hundreds or even thousands of years as stable soil organic matter (SOM). Forest soils, in particular, have the potential to store significant amounts of C, however, the amount of C sequestered and the carbon-to-nitrogen (C/N) ratio of soil organic matter (SOM) depend on the vegetation influencing the soil. In the last decades, mixed stands have aroused great interest among the scientific community, but it is still necessary to intensify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Therefore, composite samples as in Cools et al (2014) may hide understory effects such as those demonstrated in Rodríguez et al (2009) The different topsoil organic matter described at the stand level (previously reported by López-Marcos et al, 2018) and at a smaller spatial scale (just described here) could be linked to various trends in tree density and basal area at both spatial scales (López-Marcos et al, 2021c). The impact of different mixing percentages of stands on soil organic matter also in uences, as reported by Getino-Álvarez et al (2023). This is because, as suggested by Yeste et al (2021), not only litterfall production but also root systems and secretions may play a crucial role.…”
Section: Topsoil Organic Matter Heterogeneity Fine-scale Vs Large Sca...mentioning
confidence: 68%
See 2 more Smart Citations
“…Therefore, composite samples as in Cools et al (2014) may hide understory effects such as those demonstrated in Rodríguez et al (2009) The different topsoil organic matter described at the stand level (previously reported by López-Marcos et al, 2018) and at a smaller spatial scale (just described here) could be linked to various trends in tree density and basal area at both spatial scales (López-Marcos et al, 2021c). The impact of different mixing percentages of stands on soil organic matter also in uences, as reported by Getino-Álvarez et al (2023). This is because, as suggested by Yeste et al (2021), not only litterfall production but also root systems and secretions may play a crucial role.…”
Section: Topsoil Organic Matter Heterogeneity Fine-scale Vs Large Sca...mentioning
confidence: 68%
“…On the other side, the C/N ratio, a proxy of the lower quality of organic matter (Yeste et al 2021;Getino-Álvarez et al 2023) increased towards the negative end of PC2, meaning that the highest organic matter quality is found in the subplots towards the positive end of PC2. bD over the PC2 is likely to be an indirect effect of the change of the soil's physical properties associated with the formation of aggregates during organic matter decomposition (Prescott and Vesterdal 2021) and, therefore, provides here similar information as C/N.…”
Section: Topsoil Organic Matter Heterogeneity Fine-scale Vs Large Sca...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the decomposition of the siderate biomass, rich in carbohydrates and proteins, occurs much faster than straw, which has a higher content of aromatic compounds of phenolic nature in its composition and a wide C:N ratio ( Getino-Álvarez et al, 2023 ). The presence of straw in combination with siderates has a notable effect: it retards the decomposition of the green siderate mass, leading to favourable conditions for humus accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…A similar situation was observed in greyzemic phaeozems, where the combined application of wheat straw with cover crops, manure, and mineral fertilisers increased the activity of CO 2 release by 39.8-48.1%. 10.3389/fmicb.2023.1287701 It is known that the decomposition of the siderate biomass, rich in carbohydrates and proteins, occurs much faster than straw, which has a higher content of aromatic compounds of phenolic nature in its composition and a wide C:N ratio (Getino-Álvarez et al, 2023). The presence of straw in combination with siderates has a notable effect: it retards the decomposition of the green siderate mass, leading to favourable conditions for humus accumulation.…”
Section: Resultsmentioning
confidence: 99%